Php jQuery cookbook : over 60 simple but highly effective recipes to create interactive web applications using PHP with jQuery - Joshi, Vijay (Packt Pub., 2011)
Annotation As web technology evolves, the gap between desktop applications and web applications continues to vanish. And what better way to bridge that gap, for your own website, than using the best two open source technologies in the market: PHP and jQuery. The power-combo of these two is leading the way in revolutionizing the RIA world. Although they are easy to integrate, finding or figuring out how to do what you want to do is rather arduous. The PHP jQuery Cookbook will be your handy guide with walkthroughs of common integration tasks and problems that will help you master the possibilities available using the PHP and jQuery combo. You will learn quick solutions to necessary tasks to integrate the power of two of the best known and most widely used web technologies of today _ PHP on the server side and jQuery on the client side. Glide through the basics and move to advanced topics to create dynamic and interactive web applications with this book in hand. This book covers a wide array of technical aspects of creating an interactive website. Apart from basics of PHP and jQuery, you will go through advanced topics like creating plugins, validating controls, and useful utilities that you will be able to use as stand-alone tools. AJAX, the key technique of browser-server communication is covered in detail. You will also learn to use JSON, which is becoming preferred as a mode of data interchange over XML, both in web applications and web services. The book also covers database interaction, which is an important part of any dynamic web application. You will also gain expertise in debugging JavaScript with the help of useful tools that will save you hours of tedious manual debugging. Most importantly, by using jQuery and PHP together, you will be able to develop applications that are compatible with all major browsers, with no need to write code targeted at specific browsers! A package of comprehensive solutions to problems that may occur while building web applications with PHP and jQuery.
Includes index.
Keywords: PHP (Computer program language) -- Handbooks, manuals, etc.; Web site development -- Handbooks, manuals, etc.; JavaScript (Computer program language) -- Handbooks, manuals, etc.; elektronické knihy; electronic books